PENGARUH DUKUNGAN ORGANISASI DAN PEMBERDAYAAN KARYAWAN TERHADAP KINERJA KARYAWAN (STUDI PADA KARYAWAN BAGIAN UMUM RSUD ARIFIN ACHMAD PROVINSI RIAU) - Intan Pertiwi; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine the effect of organizational support and employee empowerment on employee performance partially and simultaneously. This study uses a questionnaire as a tool for collecting data distributed to 49 respondents to the employees of the General Section of Arifin Achmad Hospital in Riau Province. The data is then processed using descriptive analysis and statistical analysis using SPSS 17.0 by conducting validity tests, reliability tests, simple linear regression analysis, multiple linear analysis, analysis of determination (R2) and hypothesis testing by testing t test (partial) and F test (simultaneous ). The results showed that the first hypothesis testing was organizational support for employee performance, t count (5,762)> t table (2,011), meaning that organizational support had a significant effect on employee performance. Second, employee empowerment is t count (5,206)> t table (2,011), meaning that employee empowerment has a significant effect on employee performance. The results of the F test count (29,191)> F table (3,20), meaning that organizational support and employee empowerment simultaneously have a significant effect on employee performance. Keywords: Organizational Support, Employee Empowerment, Employee Performance